Plan de marketing para la microempresa "Vane's Food" - Padilla, Jéssica L. (2019)
The main objective of this research project was to design a marketing plan for the implementation of new commercial strategies in the VANE'S FOOD microenterprise, with the aim of enabling microenterprises to promote and commercialize their products through new tools digital, it also proposes an administrative restructuring of the company and a redesign of the brand in every sense. In this way, achieve sufficient efficiency and effectiveness from the administrative area to the promotion and sales processes, which allows positioning the product locally and promoting it internationally. This plan was based on the theoretical basis proposed by the father of marketing "Philip Kotler" in his works "Marketing moves 2002" and "Digital Marketing 4.0 2016", where he talks about the use and importance of new digital tools , such as; social networks, web pages and digital platforms, each of them aimed at the development of digital marketing. The improvement in the administrative processes was also considered, always seeking the optimization of resources and finally an international market study was carried out which allows to determine the most suitable country for a later promotion and sale of the product, in this way to expand the portfolio of clients towards an international market, increase production levels, thereby economically improving profits for owners as well as employe es and collaborators of the company.